Circulating-tumor DNA as predictor of enzalutamide response post-abiraterone treatment in metastatic castration-resistant prostate cancer. (2020) - Moses, Marcus; Niu, Alex; Lilly, Michael B.; Hahn, Andrew W.; Nussenzveig, Roberto; Ledet, Elisa; Manogue, Charlotte; Cotogno, Patrick; Lewis, Brian; Layton, Jodi; Agarwal, Neeraj; Sartor, Oliver; et al.
Abstract : Novel AR-directed therapies abiraterone acetate (AA) and enzalutamide (ENZA) are effective agents improving overall survival within metastatic castrate-resistant prostate cancer (mCRPC). Upon progression, subsequent administration of other AR-axis targeted agents has in general, limited activity. The presence of somatic androgen receptor (AR) alterations is associated with resistance to AR-targeted therapies, but there has been minimal investigation into the association of AR alterations with response to ENZA post-AA. This multi-institutional retrospective analysis was designed to further examine the role of genomic alterations in the AR gene as a biomarker of responsiveness to ENZA in the post-AA setting. In this dataset, approximately one third achieved a serological response with a short time to PSA progression of less than two months. Alterations in the AR gene were detected in subset of these patients and the lack of AR alterations was associated with a statistical improvement in PSA responses to ENZA. Further consideration into elucidating the genomic landscape of mCRPC tumors can potentially provide insight into determining which AR aberrations are contributing to the cross-resistance in sequential AA and ENZA. Abstract: Background: The crossover from abiraterone acetate (AA) to enzalutamide (ENZA) is a frequent approach in clinical practice. Our aim was to explore the role of genomic alterations as putative biomarkers of response to sequential AA followed by ENZA in mCRPC and their association with clinical outcomes. Patients and methods: This was a multi-center, retrospective analysis of mCRPC patients with circulating-tumor DNA (ctDNA) post-AA and prior to ENZA treatment. Objectives of this analysis were to assess PSA response, time to PSA progression (TTP) and overall survival (OS) in mCRPC patients treated with ENZA following progression on AA with respect to genomic aberrations detected by ctDNA. Results: A total of 28 patients with mCRPC were identified. Median time between AA and ENZA was 3.1 months and median initial PSA prior to ENZA was 35.0 ng/mL. Nine patients (32.1%) achieved PSA responses to ENZA. Most patients (79.0%) achieved confirmed PSA progression with median TTP of 1.6 months (95% CI, 0.7–2.4). Somatic alterations in AR genes were detected in 36.0% of patients with other common alterations detected including 39.0% TP53, 11.0% DNA repair, and 11.0% PTEN. A lack of AR alterations was associated with better PSA response to ENZA ( p  = 0.04). Conclusion: While lack of AR alterations in ctDNA was associated with more favorable outcomes, the present dataset is insufficient to recommend the use of ctDNA to impact clinical decision-making in this setting. Further understanding of the implications of the genomic phenotype in ctDNA of castration-resistant tumors and the potential therapeutic implications is required.